Maggot (Hermetia illunces) sebagai pakan alternatif pada budidaya ikan - Mokolensang, Jeffrie F.; Hariawan, Mutiara G. V.; Manu, Lusia (e-Journal BUDIDAYA PERAIRAN, 2018)
In increasing fish farming production, it is very dependent on the availability of fish feed which has recently been expensive. To overcome this, was necessary to find alternative feeds that have nutritional value according to the needs of cultivated organisms. Maggot (Hermetia illucens Linn.) is a black soldier fly larvae that has a chewy texture, high protein and has the ability to secrete natural enzymes that help improve the digestive system of fish. . The aimed of this research was to find out the amount of maggot (H. illucens Linn.) production in several cultivation media with different treatments. The Â results of the study found that it took up to 2 weeks to produce maggot that had ready to be used as feed. Maggot had the potential to be cultivated as an alternative to fish feed.